Effects of the COVID-19 Pandemic on the Success of Traditional Small and Medium Enterprises (SMEs): An Investigation of the Footprints of Economic Crisis Attributable to COVID-19 - Khaliq, Anum; Ali, Shunaid; Chen, Ziyi; Kanwal, Sehrish; Khan, Farina; Niazi, Abdul Aziz Khan; Chen, Leping (Frontiers in Psychology, 2022)
The COVID-19 pandemic created a significant economic decline and altered market behavior, forcing buyers and dealers online. The traditional local market merchants are not fully equipped with e-commerce business techniques and strategies, which is a barrier to their e-commerce behavior and success. The study aims to help small-medium firms adapt to an uncertain economic environment instead of reducing or shutting down business-like in Pakistan. From health to education, economy to domestic and social protection, various researches have been done since 2020. The researcher used primary data sources and did a Quantitative study after collecting the 240 samples size of data from the successful e-commerce players of Pakistan. The results confirm that customer satisfaction is essential for entrepreneurs to succeed, as customers were not satisfied with online shopping during COVID-19. Customer knowledge management (CKM) and job satisfaction (JS) are studied as potential and realized capacity variables. CKM act as a strategic asset to collect and assimilate the external customer knowledge. In contrast, satisfied employees act as a valuable asset that dynamically responds to changing customer needs and business environment by efficiently utilizing their knowledge and skills and reaching business success which is mirrored in customer satisfaction. Conclusive results enable practitioners to perceive the business success during economic crises in the organization’s absorptive capacity.